Understanding the concept of muslimah spa among the workers of spa at bandar Puncak Alam / Azizah Mohd Zan - Mohd Zan, Azizah (2019)
Muslim spa is a spa that adheres to Islamic shariah. Another term for spa is the beautification industry, beauty center, wellness and care spa and Islamic spa practices. Spa is the form or term from Latin which is “Solus Per Aqua” that means healing with water in Latin and that the concept of treatment. Issues that arise in the beauty industry are often consumer doubts in the use of products in spa treatments. Issues related to care genitalia also applies when receiving treatment at the spa. Muslim spas are created for Islamic consumers of Islam and especially for women. Women and beauty are inseparable. Therefore, this study is designed to explain the concept of Muslim spa in terms of treatment offered and the types of spa. Among the treatments provided at the spa are generally massage, body bathing, body scrub, sauna, facial and hair treatment. The spa also has many types, including hotel spa, medical spa, and day spa. In addition, this study also examines the elements involved in spa activities such as the use of halal products, genital care and the treatment activities involved. This study is focused on a Muslim spa in the Puncak Alam area. The purpose of this study is to gain an understanding of the concept of the Muslim spa in Puncak Alam area. Explanations are supported by previous studies and several articles of relevance. Then the researcher used the arguments from the Qur'anic verse as supporting arguments. This research use the qualitative methodology which is based on interviews and internet search. Most Muslim women in Malaysia will seek Muslim spas for beauty and health care as they keep their genitals closed while receiving treatment.